Kajian Karakter Ketahanan terhadap Cekaman Kekeringan pada Beberapa Genotipe Bibit Kelapa Sawit (Elaeis guineensis Jacq.) - Endah Retno Palupi; Yopy Dedywiryanto (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
The research was aimed to study the response of oil palm seedlings to drought stress and to determine characters which would be useful in selection for drought resistance. This research was conducted at PT Dami Mas Sejahtera field station and SMART Research Institute laboratory Libo, Riau from April to August 2005. The research was arranged in split plot design with two factors in randomized block design. The main plot was soil water content, i.e. 100%FC/field capacity : 24+1%; 75%FC : 18+1%; 50%FC : 12+1%; and 25%FC : 6+1%, whereas the subplot was four genotypes: G1: 635xAP.01, G2: 635x742.316, G3:15x742.316 and G4: 15xAP.01. The result showed that only soil water content as low as 25%FC could significantly inhibit seedling growth, as indicated by reduction of leave water content, shoot and root dry weight, seedling height, root length and volume; and an increase of water deficit. Soil water content ranging from 50-100% FC did not give any significant effect. Based on the physiological responds, G1 and G3 were relatively more resistant to drought stress than G2 and G4. Leaf water content was the easiest, cheapest, fastest and non-destructive variable to be used for early selection of drought resistant oil palm seedlings. Key words: Oil palm, seedling, character for selection, drought resistant